Studies on the life of Muhammad and the dawn of Islam: idol worshippers, Christians and Jews in pre- and early Islam - Lecker, Michael (Variorum collected studies, 2023)
"This volume includes twenty articles published between 1994 and 2020 on the subject of Muhammad and the history of early Islam, covered in five sections: Arabia on the Eve of Islam, Muḥammad at Medina, Muḥammad and the Jews, Muḥammad ibn Isḥāq and the sīra and Studies on Early Islamic Literature. The book focuses on a variety of historical questions, from the presumed Ghassanid/Byzantine involvement in the hijra and Muḥammad's treaties with the main Jewish tribes. Predilection for detail, especially in the realms of genealogy and geography, is a salient characteristic of Lecker's research, which in recent years has been increasingly based on digitized text repositories. Many of the articles deal with the social and economic environment or early Islam, which is vital for the study of Muḥammad's biography. They are conceived of as building blocks in a future, refined and critical biography of the Arabian prophet. Studies on the Life of Muhammad and the Dawn of Islam will appeal to those interested in the history of pre- and early Islam, with an emphasis on Muḥammad's life and his relations with the Jews of Arabia"--